Game of Words for Cognitive Test Results in Class 2 Citizenship Education Learning in Elementary Schools: Permainan Kata Bersambut Terhadap Hasil Tes Kognitif dalam Pembelajaran Pendidikan Kewarganegaraan Kelas 2 di Sekolah Dasar - Muarofah, Zhumrotul Rohmatin; Kurniawan, Machful Indra (Universitas Muhammadiyah Sidoarjo, 2023)
This researcher in the background of the facts in the field that class II SDN Pejangkungan there are some students have difficulty with intellectual ability. The purpose of this study was to determine the influence of the use of the game of greeting words on the results of cognitive tests in learning civics class II in elementary school. This study uses quantitative experimental research methods with nonequivalent control group design. The results of hypothesis testing using paired sample T - Test t-Test obtained the value of the count of cognitive test results = 11.235> ttable 2.045. So it can be concluded that there is an influence on the media of word games and letter cards to the results of cognitive tests in learning PKN Class II in elementary school.